Adolescent use of opioids and stimulants: testing the influence of peers, self-control, and sports participation - Schaefer, Brian P. (Criminal justice studies, 2017)
Over 15% of adolescents in the US have used opioids or stimulants in the past year without a prescription. Research suggests that sports participation is a predictor of adolescent illicit opioid and stimulant use; however, these studies are atheoretical. This study fills this gap by using a national sample to use social learning theory and self-control theory, to examine adolescent use of nonmedical opioids and stimulants. The study also examines the relationship between sports participation and drug use. Findings indicate social learning and low self-control predicts adolescent use of stimulants and opioids; however, sports participation was not significant. The manuscript concludes by discussing the finding’s implications.